Coordination failure among multiple lenders and the role and effects of public policy - Kasahara, Tetsuya (Journal of Financial Stability, 2009)
This paper analyzes the role and effects of public policy when inefficient financing can result from coordination problems among multiple lenders. Developing a financing game with both fundamental and strategic uncertainty, we first show that inefficient liquidation of a fundamentally solvent project can arise in equilibrium as a result of coordination failure among lenders. We then investigate the effects of two types of public policies: an information policy and a public guarantee program. The analysis shows that the inefficiencies caused by coordination problems among lenders can be effectively and efficiently removed only when both policies are simultaneously designed and implemented in an appropriate combination. We also address the potential cost of public intervention, focusing particularly on the negative influence on the ex ante effort incentives of borrowers.